National Health Service : The Government's Policy (White Paper)
1944-01-03 1944 1940s 5 pages PRIVATE AND CONFIDENTIAL J.W.C.&.F.C.AND S.I.C.4/1 1st March, 1944. NATIONAL HEALTH SERVICE The Government's Policy (White Paper) The Government's health policy as set out in the White Paper is a considerable advance on present medical services but it is not a comprehensive Health National Service. Various Government departments will apparently still deal isolatedly with different medical subjects. There are still many gaps left wide open. The best part of the scheme is the proposed reform of Medical Administration, central and regional. There is a studied attempt quite rightly to achieve uniformity and agreed standards by the necessity of securing the Minister's approval to any area reforms. As far as the ordinary patient is concerned, the medical services will be equally available to all citizens without charge. HOSPITAL SYSTEM The dual hospital system is to continue although it is admitted that "a fully organised system of hospitals will be the keystone of the National Health Service." The future hospital service will include institutional accommodation for every type of disease and treatment including those for the chronic sick and for rehabilitation and be ready of access for appropriate cases. Ancillary hospital services for diagnosis and treatment will be provided. 1. It is admitted that the two main hospital systems should "work closely together in future for a common purpose" - in "the fullest co-operation." 2. The areas of the country suitable for hospital organisation be determined and settled so as to get all hospitals working in team spirit, "planned as a wider whole", so that each case may be appropriately to the best suitable hospital, "not necessarily the local one", even to specialist centres. One single local authority will have this duty of organisation. This involves some local Government changes so as to secure Joint Health Authorities for the determined areas (instead of as at present each L.A. County or County Borough Council exercising its powers on its own). County and County Boroughs are not large areas for the health areas envisaged for a unified hospital service (still on dual lines) proposed. For such a purpose the area must satisfy three conditions of - (a) adequate population and financial resources, having regard to economy and efficiency, (b) including both urban and rural areas in suitable balance and (c) general self sufficiency (leaving exceptional inter-area arrangements for very specialised services). So new Joint Health Authorities will be set up (Joint Health Boards) for larger areas decided on by the Minister after consultation with local interests. Some exceptional bodies, like the L.C.C. will remain as they are. All present health powers of L.A. regarding hospital services will be transferred to the new Joint Boards, who will own, administer and manage the publicly owned hospitals. 292/847/2/97